Effects of water stress on the physiological growth indices on performance of soybean genotypes - Yunusa, Mustapha; Ibraheem, Alhassan; Ibrahim, Manu (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Pot experiment was conducted at the Department of Agronomy Crop Pavilion of the University of Ilorin, Ilorinto assess the effects of water stress at different growth stages on the physiological parameters of soybean genotypes. Six soybean genotypes (TGX 536-02D, TGX 1830-2DE, TGX 1019-2EN, TGX 1740-2F, TGX 1485-1D and TGX 1817-12E) were subjected to water stress at three growth stages (vegetative, flowering and post-flowering stages) with a well-watered control. The experiment was designed as a factorial trial and laid out in split- plot arrangements. Morphological growth characters such as number of leaves, leaf area, branching and dry matter production were measured during growth which were used to determine physiological growth indices.Results show that crop growth rate (CGR), relative leaf growth rate (RLGR), net assimilation rate (NAR) and leaf area ratio measured at vegetative growth were significantly reduced by water stress occurring at the vegetative stage.Amongst the investigated genotypes TGX 536-02D was the most tolerant while 1485-1D was the least tolerant genotypes.